Stemness Enhancement of Human Neural Stem Cells following Bone Marrow MSC Coculture. Issue 4 (April 2015) - Haragopal, Hariprakash; Yu, Dou; Zeng, Xiang; Kim, Soo-Woo; Han, In-Bo; Ropper, Alexander E.; Anderson, Jamie E.; Teng, Yang D.
Rapid loss of stemness capacity in purified prototype neural stem cells (NSCs) remains a serious challenge to basic and clinical studies aiming to repair the central nervous system. Based on the essential role of mesodermal guidance in the process of neurulation, we hypothesized that coculture of human NSCs (hNSCs) with human bone marrow-derived mesenchymal stromal stem cells (hMSCs) could enhance the stemness of hNSCs through Notch-1 signaling. We have now tested the hypothesis by assessing behaviors of hNSCs and hMSCs under systematically designed coculture conditions relative to monocultures, with or without Notch-1 manipulation in vitro. Our data demonstrate that expression levels of Notch-1 and Hes-1 as determined by immunocytochemistry are significantly higher in hNSCs cocultured with hMSCs than those of controls. Furthermore, coculturing significantly increases immunoreactivity of CD15, a neural stemness marker, but decreases CD24, a marker of neural/neuronal commitment in hNSCs. The effect is independent from the physical status of cell growth since coculture and notch signaling actually promotes hNSC adhesion. Importantly, coculture with hMSCs markedly augments hNSC proliferation rate (e.g., higher yield in G2 /M phase subpopulation in a notch-dependent manner detected by flow cytometry) without diminishing their lineage differentiation capabilities. The results suggest that coculture of hNSCs with hMSCs enhances stemness biology of hNSCs partially via activation of Notch-1 signal transduction. Our finding sheds new light on mesoderm-ectoderm cell fate determination via contact-based hMSC-hNSC interactions and provides mechanistic leads for devising effective regimens to sustain and augment stemness of in vitro established hNSC and hMSC lines for basic science, translational and clinical applications.